Differential Expression Levels Assessment of Avian E2A Gene in Two Chinese Indigenous Duck Breeds (Anas platyrhynchos) by Semi-Quantitative RT-PCR - Mekki, Dafaalla M.; Liang-yong, Bian; Jin-yu, Wang; Yan, Yang; Lin-chuan, Li; Yabo, Yu; Musa, Hassan H. (International Journal of Poultry Science, 2006)
Semi-quantitative polymerase chain reaction (RT-PCR) was applied to quantify and compare variations in avian E2A expression level between two Chinese indigenous duck breeds for different tissues. Six primer combinations in addition to β-actin as an internal control were used. The expression level of E2A was significantly higher (p< 0.05) in kidney tissues than lung tissues for both Gao you and Kun shan indigenous duck breeds. The variability of gene expression between two breeds showed 34.35% and 60.70% higher expression in Gao you breed than Kun shan breed for kidney and lung tissues, respectively. Differences were found to be significant (p< 0.05) only for expression level in lung tissues. No significant effect of sex upon E2A expression was detected.